THE EFFECT OF THE HOTS-BASED DISCOVERY LEARNING MODEL ON STUDENTS' CRITICAL THINKING ABILITIES IN QUADRANGLE AND TRIANGLE PLANE FIGURES - Putri, Rizky Sundari (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
The discovery learning model is a learning strategy that encourages students to conduct observations, experiments, and scientific actions to achieve a deeper understanding. In this model, students are active in finding and understanding the concepts taught, as well as solving problems by collecting and processing data. This study aims to determine the effect of the use of HOTS-based discovery learning model on students' critical thinking skills on the material of quadrilaterals and triangles. The population in this study were grade IX students at MTs Az-Zahroh. The sample in this study were 23 students of grade IX Ibnu Khaldun (as the experimental class) and 23 students of IX Ibnu Sina (as the control class). The research method used in this study was a quasi-experimental one. The research instrument used a question validation sheet and an essay-shaped test (description) on the material of quadrilaterals and triangles. The data analysis technique used was the normality test. The research hypothesis test used the t-test, namely the independent sample t-test and the paired sample t-test with the help of the SPSS 25 application. The results of the independent sample t-test obtained a Sig. value. (2-tailed) of 0.000 < 0.05, which means H0 is rejected and Ha is accepted. Therefore, there is a difference in the test results of students' critical thinking abilities using the HOTS-based discovery learning model and those using the conventional teacher-centered learning model. In the paired sample t-test, Sig. (2-tailed) pair 1 = 0.000 and pair 2 = 0.026, meaning the significance value is < 0.05, thus proving that H0 is rejected and Ha is accepted. Therefore, it is clear that there is a difference in the average pretest-posttest between the experimental and control classes. Therefore, it can be concluded that the HOTS-based discovery learning model has an effect on students' critical thinking abilities, especially regarding quadrilaterals and triangles.Keywords: Influence, HOTS-Based Discovery Learning Model, Student Critical Thinking, Mathematics Learning